Dual-phase electrocatalysts for hydrogen evolution reaction: A synergistic approach to enhance catalytic activity and durability - Asad Ali Shah Zaidi; Zeeshan Ahmad; Iqbal Nisa; Sumayya Mumtaz (Vietnam Journal of Science, Technology and Engineering)
Sustainable hydrogen production depends on optimising the hydrogen evolution reaction (HER); however, the development of scalable and efficient electrocatalysts remains challenging, particularly in alkaline environments where catalyst degradation and slow reaction kinetics limit performance. This review explores the promising potential of dual-phase electrocatalysts, which integrate complementary materials to synergistically enhance catalytic activity and stability. Focusing on processes in alkaline media, recent progress in HER catalysts has utilised advanced techniques such as hollow nanostructures, metal doping, and atomic layer deposition (ALD). Key materials, including transition metal phosphides, oxides, and dichalcogenides, demonstrate notable advancements in electron transport and hydrogen adsorption, thereby enhancing HER efficiency. The challenges of scaling these materials for commercial application are also addressed, with an emphasis on how the integration of computational and experimental approaches could accelerate catalyst design. Consequently, dual- phase catalysts represent a viable pathway for cost-effective and efficient hydrogen production, supporting the transition to a hydrogen-driven energy future.